Handbook of research on positive organizational behavior for improved workplace performance - Baykal, Elif, 1983- (Advances in human resources management and organizational development (AHRMOD) book series., 2020)
"This book examines the effectiveness of positive psychological interventions to increase individual happiness, organizational harmony, and corporate performance"--